المعارضات العقلية المعاصرة الواردة على احاديث بدء الوحي دراسة نقدية - شراد, هناء (University of Eloued-جامعة الوادي, 2022)
"المـــلخص : تبين هذه الدراسة المعارضات العقلية المعاصرة لحديث بدء الوحي وتوضح طعن المغرضين في صحة الحديث مستدلين في قولهم بأن الروايات الواردة في ذلك متعارضة مع بعضها، حيث جمعت كل هذه الشبهات والطعون على حديث بدء الوحي وتناقشها مناقشة علمية بعيدا عن التحيز والهوى من خلال إخضاعها لأصول النقد الحديثي وقواعد البحث العلمي من أجل الوقوف على مدى بطلان أقوال هذه الطائفة كما تبين كشف سقيم فهمهم لهذا الحديث.""Abstract: This study shows the contemporary mental oppositions to the hadith of the beginning of the revelation and clarifies the challenge of those who are interested in the authenticity of the hadith, citing their saying that the narrations contained in that contradict each other, as all these suspicions and challenges to the hadith of the beginning of the revelation are collected and discussed in a scientific discussion away from bias and whims by subjecting them to the foundations of modern criticism And the rules of scientific research in order to determine the extent of the invalidity of the sayings of this sect, as revealed their poor understanding of this hadith. "
مذكرة ماستر
Keywords: المعارضات العقلية- حديث بدء الوحي - الردود; mental oppositions -Hadith of the beginning orepliesf revelation -